Host protective ASP-based vaccine against the parasitic nematode Ostertagia ostertagi triggers NK cell activation and mixed IgG1-IgG2 response - González-Hernández, Ana (Sci Rep, 2016)
The mucus-dwelling parasite Ostertagia ostertagi is one of the most important gastrointestinal nematodes in cattle. Our group has previously demonstrated the protective capacity of a vaccine against this parasite based on a native activation-associated secreted protein ASP1 (nASP) in combination with the saponin adjuvant QuilA. The aim of the current study was to analyse the effect of both antigen and adjuvant on the cellular and humoral vaccine-induced immune responses by comparing the native ASP to a recombinant version expressed in Pichia pastoris (pASP) and replacing QuilA by Al(OH)(3). Immunization of cattle with the protective nASP+QuilA vaccine was associated with antigen-induced proliferation of natural killer (NK) cells combined with IFN-γ secretion and the induction of a mixed IgG1/IgG2 antibody response. ASP-specific activation and proliferation of NK cells was also observed in mice following the same vaccination regime. Replacing QuilA by Al(OH)(3) or nASP by pASP significantly decreased the capacity of the vaccines to trigger both NK cell activation and antibody responses and failed to induce protection against a challenge infection. Reduction of the structurally anchoring disulphide bonds of the nASP completely abolished its ability to induce NK cell activation and antibody responses, highlighting the importance of protein conformation for the immunostimulatory activity.